CORPORATE BOARD AND GOVERNANCE STRUCTURE IN UZBEKISTAN COMPARED WITH COMMON LAW COUNTRIES PRACTICE (UNITED STATES OF AMERICA AND UNITED KINGDOM) - Koryogdiev Bobur Umidjon ugli (Galaxy International Interdisciplinary Research Journal, 2021)
This article demonstrates weaknesses of general corporate governance practices in the Republic of Uzbekistan through a comparative analysis of existing corporate governance practices in the US and the UK. At the same time, it puts forward suggestions that may contribute to the development of the industry and may be consistent with existing corporate governance relationships. Our comparative study is a collection of valuable data on the general principles of corporate governance in each of the above countries, corporate board and governance structure. Using functional and structural methods of comparison, our study first describes the data on the practices of the Republic of Uzbekistan, then the existing systems in the Anglo-Saxon countries and lists their differences and similarities. The article concludes with a number of suggestions which are close to reality and could be a solution to the problems in this area in our country.The research results show that the corporate governance model in Uzbekistan is modeled on the German model, and takes place through a two-tier board structure. In the precedent countries, governance is largely unitary, with a large number of independent board members, a unified management structure and relative gender diversity.